Spatiotemporal Dynamics of β-Adrenergic cAMP Signals and L-Type Ca2+ Channel Regulation in Adult Rat Ventricular Myocytes - Leroy, Jerome (2008)
Steady-state activation of cardiac β-adrenergic receptors leads to an intracellular compartmentation of cAMP resulting from localized cyclic nucleotide phosphodiesterase (PDE) activity. To evaluate the time course of the cAMP changes in the different compartments, brief (15 seconds) pulses of isoprenaline (100 nmol/L) were applied to adult rat ventricular myocytes (ARVMs) while monitoring cAMP changes beneath the membrane using engineered cyclic nucleotide-gated channels and within the cytosol with the fluorescence resonance energy transfer–based sensor, Epac2-camps. cAMP kinetics in the two compartments were compared to the time course of the L-type Ca2+ channel current (ICa,L) amplitude. The onset and recovery of cAMP transients were, respectively, 30% and 50% faster at the plasma membrane than in the cytosol, in agreement with a rapid production and degradation of the second messenger at the plasma membrane and a restricted diffusion of cAMP to the cytosol. ICa,L amplitude increased twice slower than cAMP at the membrane, and the current remained elevated for ≈5 minutes after cAMP had already returned to basal level, indicating that cAMP changes are not rate-limiting in channel phosphorylation/dephosphorylation. Inhibition of PDE4 (with 10 μmol/L Ro 20-1724) increased the amplitude and dramatically slowed down the onset and recovery of cAMP signals, whereas PDE3 blockade (with 1 μmol/L cilostamide) had a minor effect only on subsarcolemmal cAMP. However, when both PDE3 and PDE4 were inhibited, or when all PDEs were blocked using 3-isobutyl-l-methylxanthine (300 μmol/L), cAMP signals and ICa,L declined with a time constant >10 minutes. cAMP-dependent protein kinase inhibition with protein kinase inhibitor produced a similar effect as a partial inhibition of PDE4 on the cytosolic cAMP transient. Consistently, cAMP-PDE assay on ARVMs briefly (15 seconds) exposed to isoprenaline showed a pronounced (up to ≈50%) dose-dependent increase in total PDE activity, which was mainly attributable to activation of PDE4. These results reveal temporally distinct β-adrenergic receptor cAMP compartments in ARVMs and shed new light on the intricate roles of PDE3 and PDE4.